Selective head cooling or whole body cooling? That is the question - Vlad Dima; Roxana-Elena Bohiltea; Raluca Mariana Stanescu; Adrian Toma; Valentin-Nicolae Varlas; Ana-Maria Davitoiu (Amaltea Medical Publishing House, 2022)
Background. Studies to date support the beneficial effect that therapeutic hypothermia (TH) has on neonates with hypoxic-ischemic encephalopathy. TH can be delivered in two ways: selective head cooling (SHC) or therapeutic whole-body cooling (WBC). The purpose of this review is to examine the literature to expose the advantages and disadvantages of the two methods of performing TH in neonates diagnosed with moderate or severe HIE and to investigate whether one method is superior to the other. Methods. We started from the data from the Cochrane review published in 2013 [1] and we want to bring new information from recent clinical studies comparing the two TH methods (SHC vs WBC). Clinical studies were searched and analyzed by a single individual (through dedicated search engines such as Google Scholar, PubMed, and Scopus). We have included clinical studies from the last 7 years comparing the two ways of performing TH (SHC vs. WBC). We selected only the articles that compared the two methods and excluded the articles describing only one method. Results. After excluding the clinical trials that did not meet the eligibility criteria, 5 clinical trials remained (n = 256 neonates). Analysis of these studies supports the idea that both modalities of therapeutic hypothermia cool central nervous system (CNS) structures and have a similar neurodevelopmental prognosis among surviving neonates. Also, there are no significant differences in terms of short-term neurological prognosis, as well as the adverse effects that may occur in neonates with moderate or severe HIE (hypoxic-ischemic encephalopathy) treated with SHC or WBC; although some studies note the presence of more severe, statistically significant lesions among patients treated with SHC compared to those treated with WBC. Conclusions. Prospective, randomized studies on a much larger scale are needed to track the adverse effects that the two HT methods may have on patients, as well as long-term neurological and cognitive prognosis. Until now, there is no clear evidence that one of these two methods is definitely safer or more reliable than the other.